1987
DOI: 10.3168/jds.s0022-0302(87)80188-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood Studies and Performance Among Calves Reared by Different Methods

Abstract: Three methods of feeding calves were compared as follows: 1) milk replacer only with restricted movement, 2) milk replacer only with freedom of movement, and 3) hay, grain, and water with freedom of movement. No significant differences were noted for variables of acid-base balance (sampled while resting). An Fe deficiency, microcytic, hypochromic anemia, developed in the calves receiving milk replacer only. Average daily gain, carcass grade, and sale price were superior for calves receiving only milk replacer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 6 publications
6
18
0
2
Order By: Relevance
“…In growing calves feeding and rearing system has an important influence on the values of haematological variables (Reece & Hotchkiss, 1987;Scheidegger, 1973). Influence of feeding regime becomes more apparent after the 5 th week when consummation of dry food (hay, starter) increases.…”
Section: Haematological Variables In Calvesmentioning
confidence: 99%
See 2 more Smart Citations
“…In growing calves feeding and rearing system has an important influence on the values of haematological variables (Reece & Hotchkiss, 1987;Scheidegger, 1973). Influence of feeding regime becomes more apparent after the 5 th week when consummation of dry food (hay, starter) increases.…”
Section: Haematological Variables In Calvesmentioning
confidence: 99%
“…In older studies the blood cells were counted manually with Neubauer chambers, PCV values were estimated with centrifugation in microhaematocrit tubes, and Hb concentration was measured photometrical (Greatorex, 1954;Hanschke & Schulz, 1982). In later studies the blood cell numbers were counted with automated counters from different producers, PCV value was still estimated by microhaematocrit method (Scheidegger, 1973;Terosky, 1997;Steinhardt & Thielscher, 2000a;Steinhardt & Thielscher, 2000b;Reece & Hotchkiss, 1987). In most of recent researches, which were published in last years the haematological variables were measured with various automated counters (Egli & Blum, 1998;Muri et al, 2005;Knowles et al, 2000;Klinkon et al, 2000;Mohri et al, 2007, Heidarpour Bami et al, 2008.…”
Section: Haematological Variables In Calvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, countries such as the United States overtly disagree with confinement rearing systems. Studies have demonstrated that this kind of system alters calves' behavior, causing psychological and physical damage (Reece & Hotchkiss, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Für die Festlegung von Grenzwerten physiologischer Variablen in Verbindung mit tiergerechten Haltungsbedingungen und für einen Vergleich von Haltungsvarianten ist es von Interesse, welche auf das Lebensalter und die Entwicklungsqualität bezogenen Anpassungsvorgänge bei den Kälbern vorkommen können und wie diese durch Haltungsvarianten beeinflußt werden. Verfolgsuntersuchungen an Kälbern unterschiedlichen genetischen Materials während der ersten Lebenswochen sind an kleinen Tiergruppen vorgenommen (ABOUZITE et al, 1997;BOSTEDT und SCHRAMEL, 1982;GREATOREX, 1954;GUSTIN et al, 1997;MIYATA et al, 1984;OLTNER und BERGLUND, 1982;SCHLERKA, 1998;TENNANT et al, 1974), mittlere Änderungen von Variablen nachgewiesen und Einflüsse des genetischen Materials sowie von Haltungsvarianten aufgezeigt worden (REECE und HOTCHKISS, 1987). In einem Untersuchungsansatz, bei dem die Gruppenhaltung mit Tränkeautomatenfütterung mit einem Alter der Kälber von 14 Tagen begonnen wurde, sind Kälber im Beginn und am Ende der Gruppenaufzucht untersucht worden (STEINHARDT et al, 1997).…”
unclassified